Motivating contributions to online forums: can locus of control moderate the effects of interface cues? - Kim, Hyang-Sook; Sundar, S. Shyam (Taylor & Francis, 2015)
In an effort to encourage users to participate rather than lurk, online health forums provide authority badges (e.g., guru) to frequent contributors and popularity indicators (e.g., number of views) to their postings. Studies have shown the latter to be more effective, implying that bulletin-board users are motivated by external validation of their contributions. However, no consideration has yet been given to individual differences in the influence of such popularity indicators. Personality psychology suggests that individuals with external, rather than internal, locus of control are more likely to be other-directed and therefore more likely to be motivated by interface cues showing the bandwagon effect of their online posts. We investigate this hypothesis by analyzing data from a 2 (high vs. low authority cue) × 2 (strong vs. weak bandwagon cue) experiment with an online health community. Results show that strong bandwagon cues promote sense of community among users with internal, rather than external, locus of control. When bandwagon cues are weak, bestowal of high authority serves to heighten their sense of agency. Contrary to prediction, weak bandwagon cues appear to promote sense of community and sense of agency among those with external locus of control. Theoretical and practical implications are discussed.
Keywords: Electronic discussion groups; Internet forums; Locus of control; Bandwagon effect; Online health community; Motivation